Irreversible electroporation augments checkpoint immunotherapy in prostate cancer and promotes tumor antigen-specific tissue-resident memory CD8+ T cells - Brandon J. Burbach (Nature Portfolio, 2021)
Irreversible electroporation (IRE), a soft-tissue ablation technique used for tumour ablation, has been suggested to promote systemic immune responses. Here the authors show that IRE, followed by anti-CTLA-4 blockade, elicits the expansion of tumor antigen-specific CD8+ T cells and is associated with tissue residency and improved anti-tumor immune response in a preclinical model of prostate cancer.